2014
DOI: 10.1371/journal.pone.0092250
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila USP5 Controls the Activation of Apoptosis and the Jun N-Terminal Kinase Pathway during Eye Development

Abstract: The Jun N-terminal kinase pathway plays an important role in inducing programmed cell death (apoptosis) and is activated in a variety of contexts. The deubiquitinating enzymes (DUBs) are proteases regulating the protein stability by ubiquitin-proteasome system. Here, for the first time, we report the phenotypes observed during eye development that are induced by deleting Drosophila USP5 gene, which encodes one of the USP subfamily of DUBs. usp5 mutants displayed defects in photoreceptor differentiation. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…Consistent with allelic strength in different combinations of mutant alleles, the amounts of free polyubiquitin chains correlate with the animal lethal phases and tissue disorders. Meanwhile, loss of Drosophila USP5 has been shown to cause severe apoptosis in eye disks [23]. It is possible that small brain lobes and wing disks in close-to-null leon 1 /19-2 were due to severe apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with allelic strength in different combinations of mutant alleles, the amounts of free polyubiquitin chains correlate with the animal lethal phases and tissue disorders. Meanwhile, loss of Drosophila USP5 has been shown to cause severe apoptosis in eye disks [23]. It is possible that small brain lobes and wing disks in close-to-null leon 1 /19-2 were due to severe apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that Usp5 is required for Drosophila photoreceptor development and to investigate the underlying mechanism further, we examined signaling pathways critical for photoreceptor development. One of our candidate pathways is Notch signaling, which plays an important role in the specification of photoreceptors .…”
Section: Resultsmentioning
confidence: 99%
“…All Fly stocks were maintained at 25 °C on standard condition. The Usp5 mutant flies Usp5m/TM6B (the Usp5 9 mutant allele) were generated by P‐element hopping as described previously . ywflp; M(3)65FhsGFPFRT2A/TM6B , hs‐flp; tubGal4UASGFP/cyo; tub‐Gal80FRT2A/TM6B , E(spl)m8‐lacZ , UAS‐NotchRNAi (BL28981), and ywflp; Act>y+>Gal4,UAS‐GFP were obtained from Bloomington Drosophila Stock Center (Department of Biology, Indiana University, Bloomington, IN, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations